Níveis de proteína bruta em dietas para o pacu (Piaractus mesopotamicus) cultivado em tanques rede - Klein, Sidnei (2011)
The present study aimed evaluate the performance of pacu (Piaractus mesopotamicus) reared in cages in the Itaipu Reservoir, fed diets with different protein levels. The experiment was conducted at the Centre for Development of Technology for fish farming in cages, located along the Biological Refuge of Santa Helena - PR, for a period of 74 days. We used 2.000 fish with average weight of 150,5 ± 2,1 g distributed in a completely randomized design with five treatments and four replicates in 20 cages, with 5,0 m3 of usable volume, and the experimental unit consists of a tank with 100 fish. The treatments consisted of five extruded feeds with different crude protein levels (18,5; 20,7; 23,7; 25,6; and 28,3%). The feeding was performed three times daily until satiation of the animals. After the experiment were measured the parameters of growth performance, hematology, carcass yield and fillet chemical composition. The Average final weight, weight gain and daily weight gain was statistically different (P<0,05), showing a quadratic effect. We used linear effect on feed conversion. After the derivation of the equations the average final weight was greater for fish fed 25,9% CP and greater weight gain was observed with 25,8% CP. The parameters of carcass yield showed no significant difference (P>0,05). For chemical composition only moisture and ether extract showed significant differences, showing a linear effect for both, with an inverse correlation between these parameters, as increased levels of protein in the diet increased moisture and decreased the ether extract. There were no statistical differences in the hematological and biochemical variables, showing that protein levels contained in the diets did not influence the physiological status of fish. According to the results, we recommend the use of feed containing 25,8% crude protein for pacu (P. mesopotamicus) juvenile, reared in cages system.